2017
DOI: 10.1007/s10803-017-3032-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Social Stimuli on Postural Responses in Individuals with Autism Spectrum Disorder

Abstract: This study was aimed to investigate the effects of social versus non-social stimuli on postural responses in 21 boys with autism spectrum disorder (ASD) (mean age of 11.6 ± 1.5) compared with 30 typically developing (TD) boys (mean age of 11.7 ± 1.8). Postural control of children was examined while they were standing on a force plate and viewing images of an object, male face, or female face in sequence. Each image was shown in two trials and each trial lasted for 20 s. Results indicated a significant interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Previous studies have documented the developmental progression of the ability to maintain an upright posture that is accompanied by decreases in postural sway 8 . Several studies with older children with ASD have documented deficiencies in postural control, reflected in the presence of postural sway, which is accentuated when children with ASD are viewing arousing stimuli, including complex multi-sensory and social stimuli 9 11 . Less is known about the presence of postural sway in young children with ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have documented the developmental progression of the ability to maintain an upright posture that is accompanied by decreases in postural sway 8 . Several studies with older children with ASD have documented deficiencies in postural control, reflected in the presence of postural sway, which is accentuated when children with ASD are viewing arousing stimuli, including complex multi-sensory and social stimuli 9 11 . Less is known about the presence of postural sway in young children with ASD.…”
Section: Introductionmentioning
confidence: 99%
“…ASD is characterized not only by repetitive behaviors, but also by impaired social processing, also impacting postural control. Ghanouni et al (2017) presented children with ASD and controls with social stimuli, namely pictures of neutral male and female faces (and an object), during quiet upright standing. The main finding was that children with ASD exhibited an increase in postural sway (root mean square and sway velocity) when viewing the faces.…”
Section: Cop Patterns and Asd Symptomsmentioning
confidence: 99%
“…One study has described an association between proprioceptive function and communicative autistic traits in a sample of neurotypical adult subjects [ 26 ]. In children with ASD, it has been shown that social stimuli (viewing images of human faces vs. images of objects) affected postural control [ 27 ]. One should keep in mind that posture and balance rely on more than solely proprioceptive input; they depend on complex interactions between different sensory inputs (e.g., proprioceptive, visual and vestibular inputs) and motor performance [ 28 ].…”
Section: Introductionmentioning
confidence: 99%